Words of advice: teaching enzyme kinetics - Srinivasan, Bharath (The FEBS journal, 2021)
This Words of Advice article frames the argument that enzymology is a rich discipline within the respective disciplines of mathematics, physics/chemistry and biology. It goes on to emphasize the necessity in taking an interdisciplinary approach in teaching this subject in order to gain a holistic appreciation of its various aspects. Further, it advocates the use of intuition, analogies, simulation and historical contextualization for a better appreciation of the subject matter. Enzymology is concerned with the study of enzyme structure, function, regulation and kinetics. It is an interdisciplinary subject that can be treated as an exclusive sphere of exhaustive inquiry within mathematical, physico‐chemical and biological sciences. Hence, teaching of enzymology, in general, and enzyme kinetics, in particular, should be undertaken in an interdisciplinary manner for a holistic appreciation of this subject. Further, analogous examples from everyday life should form an integral component of the teaching for an intuitive grasp of the subject matter. Furthermore, simulation‐based appreciation of enzyme kinetics should be preferred over simplifying assumptions and approximations of traditional enzyme kinetics teaching. In this Words of Advice, I outline the domain depth of enzymology across the various disciplines and provide initial ideas on how appropriate analogies can provide firm insights into the subject. Further, I demonstrate how an intuitive feel for the subject can help not only in grasping concepts but also extending it in experimental design and subsequent interpretation. Use of simulations in grasping complex concepts is also advocated given the advantages this medium offers over traditional approaches involving images and molecular models. Furthermore, I discuss the merits of incorporating the historical backdrop of major discoveries in enzymological teaching. We, at AstraZeneca, have experimented with this approach with the desired outcome of generating interest in the subject from people practising diverse disciplines.